2022
DOI: 10.1186/s12884-021-04374-4
|View full text |Cite
|
Sign up to set email alerts
|

Mental well-being during stages of COVID-19 lockdown among pregnant women and new mothers

Abstract: Background Pregnancy and early motherhood are sensitive times where epidemic disease outbreaks can affect mental health negatively. Countries and health care systems handled the pandemic and lockdowns differently and knowledge about how the COVID-19 pandemic affected the mental well-being of pregnant women and new mothers is limited and points in different directions. Aim To investigate symptoms of anxiety and depression in a population of pregnant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Psychological disturbances were always an important health parameter for pregnant women (Knight et al, 2016), which became more critical after the onset of the COVID-19 pandemic. Although one of the studies done by Overbeck et al (2022) did not find any major change in the anxiety and depression level among pregnant women after the onset of the pandemic or during different stages of it, most of the studies carried out in different parts of the globe have found anxiety and depression to be the biggest manifestation of psychological turmoil of pregnant women during the COVID-19 lockdown. An increased likelihood of depression and anxiety were observed in Belgium (Ceulemans et al, 2020), Sri Lanka (Patabendige et al, 2020), Columbia (Parra-Saavedra et al, 2020, Italy (Saccone et al, 2020), Turkey (Ayaz et al, 2020;Durankuş & Aksu, 2020;Molgora & Accordini, 2020) with relatively higher prevalence in developing countries (Durankuş & Aksu, 2020).…”
Section: Discussionmentioning
confidence: 93%
“…Psychological disturbances were always an important health parameter for pregnant women (Knight et al, 2016), which became more critical after the onset of the COVID-19 pandemic. Although one of the studies done by Overbeck et al (2022) did not find any major change in the anxiety and depression level among pregnant women after the onset of the pandemic or during different stages of it, most of the studies carried out in different parts of the globe have found anxiety and depression to be the biggest manifestation of psychological turmoil of pregnant women during the COVID-19 lockdown. An increased likelihood of depression and anxiety were observed in Belgium (Ceulemans et al, 2020), Sri Lanka (Patabendige et al, 2020), Columbia (Parra-Saavedra et al, 2020, Italy (Saccone et al, 2020), Turkey (Ayaz et al, 2020;Durankuş & Aksu, 2020;Molgora & Accordini, 2020) with relatively higher prevalence in developing countries (Durankuş & Aksu, 2020).…”
Section: Discussionmentioning
confidence: 93%
“…In October 2020, the Italian population was negatively surprised by the new increase in COVID-19 cases and the re-occurrence of restrictive lockdowns. Studies in the general population have shown a continuing effect of the pandemic and restrictions on mental health, reporting no difference, but rather a permanence of symptomatology, in women between the pandemic outbreak and later phases( Overbeck et al, 2022 ; Penengo et al, 2022 ; Ravaldi et al, 2020 ). Indeed, in some cases, the persistence of a high psychological burden and increased levels of depressive symptoms emerged in the second phase of restrictions ( Moradian S. et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Postpartum women are particularly vulnerable; pooled prevalence of postpartum depression in a meta-analysis of pandemic studies was 34% (95% CI: 21–46) (Chen et al 2022 ), though as many as 75% reported symptoms in a small US sample (Goyal et al 2022 ). In the few studies of perinatal mental health during COVID-19, there were pandemic increases in depressive (Zhang et al 2022 ) and anxious (Overbeck et al 2022 ; Zhang et al 2022 ) symptoms for postpartum women, but not pregnant women. The diverse and pervasive effects of pandemic parenting-related stressors may pose particular risk for women with a past history of peripartum depression (PPD) and put them at significant risk of relapse.…”
Section: Introductionmentioning
confidence: 99%
“…Few large studies have focused on mental health of mothers during the pandemic, and those that do are mostly cross-sectional or have a brief length of follow-up. Although there have been many longitudinal COVID-19 mental health studies (COVID-Minds Network 2021 ; Unnarsdóttir et al 2021 ), few focus on maternal mental health; all take place in Canada, Denmark, and the UK; and none specifically assess PPD history (Dickerson et al 2022 ; Ladekarl et al 2021 ; Overbeck et al 2022 ; Racine et al 2022 ; Saleem et al 2022 ; Zhang et al 2022 ). Only one Danish cohort examines symptom trajectories at multiple timepoints throughout the pandemic, and they found no differences (Overbeck et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation